The effect of mechanical constraints on gelatin samples under pulsatile flux - Blangino, Eugenia (2012)
It is of great interest in tissue engineering the role of collagen gel-based structures (scaffolds, grafts and -by cell seeded and maturation- tissue equivalents (TEs) for several purposes). It is expected the appropriate biological compatibility when the extracellular matrix (ECM) is collagen-based. Regarding the mechanical properties (MP), great efforts in tissue engineering are focused in tailoring TE properties by controlling ECM composition and organization. When cells are seeded, the collagen network is remodeled by cell-driven compaction and consolidation, produced mainly through the mechanical stimuli that can be directed selecting the geometry and the surfaces exposed to the cells. Collagen gels have different (chemical and mechanical) properties depending on their origin and preparation conditions. The MP of the collagen network are derived from the degree of cross-linking (CLD) which can be modified by different treatments. One of the techniques to evaluate MP in the network is by ultrasound (US). In this work we analyse the effect of several mechanical constraints (similar to that imposed to promote cell growth on certain sample surfaces, when seeded) on samples of gelatin with a specific geometry (thick walls cylinders) under loading conditions of pulsatile flow. We checked US parameters and estimates evolution of the network structure for different restrictions in the sample mobility. It was implemented by adapting devices specially built to measure elastic properties of biological tissues by US. The material (origin and purity) and the preparation conditions for the gelatin were selected in order to compare the results with those of literature.